Prediction of renal function upon reperfusion by ex situ controlled oxygenated rewarming. (26th October 2016) - Minor, Thomas; Sutschet, Katja; Witzke, Oliver; Paul, Andreas; Gallinat, Anja
Abstract: Background: Post‐transplant function of suboptimal kidney grafts can be improved but not accurately predicted by hypothermic machine perfusion. Therefore, a new concept of ex situ pre‐implantation machine perfusion with controlled rewarming up to subnormothermic temperatures was developed and evaluated. Materials and methods: Porcine kidneys ( n = 6/group) were retrieved before or 30 min after cardiac arrest of the donor and subjected to 18 h of static cold storage. In some cases, 90 min of machine‐controlled oxygenated rewarming (COR) was added thereafter. Functional integrity was evaluated in all kidneys by subsequent normothermic reperfusion in vitro . After supplementation of the preservation solution (Custodiol‐N solution + 5 g/L dextran 40) with 10 mg/dL creatinine, ex situ renal function was assessed by monitoring urine output, urinary creatinine and creatinine clearance at 20 °C. Functional integrity was evaluated in all kidneys by normothermic reperfusion. Results: COR resulted in a more than twofold improvement of postreperfusion creatinine clearance, oxygen consumption and enzyme release upon reperfusion, when compared with static cold storage. Predictive discrimination between kidneys with good or impaired function upon reperfusion based on parameters during perfusion at 4 °C was only moderate. This improved significantly at 20 °C. Correlation with renal clearance upon reperfusion was weak for vascular resistance at 8° ( r 2 = 0·2) and 20 °C ( r 2 = 0·41). Best correlation was found for clearance measurements at 20° ( r 2 = 0·81). Conclusions: Reconditioning by controlled oxygenated rewarming up to 20 °C improves renal function after reperfusion and can be utilized to assess graft integrity of predamaged donor kidneys.